Penguatan ApresiasiAnak Terhadap Sastra Melalui Literasi Cerita Bergambar Pada Rumah Singgah Hope Central Surabaya - Trihastutie, nopita (Fakultas Teknik, Universitas Bangka Belitung, 2023)
The purpose of this service activity is to improve soft skills, especially in terms of appreciation of children's literature. The target is children in shelter homes who are still rarely touched by literacy programs in general. This activity is a response to the low level of literacy in children in Indonesia. The focus is on literacy applications for elementary school children, especially for marginalized children in shelter homes. The expected output of the program is an increase in the ability of children in the Hope Central shelter house to appreciate children's literature through picture story literacy. The implementation of this activity consists of three stages including participants' identification and classification, visual literacy-based training, qualitative assessment, and post-training monitoring. The results of the activity show that first, some children still have difficulty reading, especially in compound sentences. Second, picture stories help children understand complex sentences and story content in independent reading sessions. Third, children are able to appreciate children's literature through picture stories. Fourth, independent reading becomes a mandatory schedule before the regular learning program in the shelter.